1996
DOI: 10.1111/j.1471-0528.1996.tb09741.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of safety and efficacy of continuous low dose oestradiol released from a vaginal ring compared with conjugated equine oestrogen vaginal cream in the treatment of postmenopausal urogenital atrophy

Abstract: Objective To compare the safety, efficacy and acceptability of a continuous low dose oestradiol releasing vaginal ring with conjugated equine oestrogen vaginal cream in the treatment of postmenopausal urogenital atrophy. Design An open, parallel, comparative multicentre trial. Setting Sydney and Melbourne, Australia. Participants and Interventions One hundred and ninety‐four postmenopausal women with symptoms and signs of urogenital atrophy were randomised on a 2:1 basis to 12 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 11 publications
0
49
0
Order By: Relevance
“…Numerous studies have reported high user acceptability of VRs for contraception and estrogen replacement therapy [29,30,[33][34][35]39,[197][198][199][200][201][202]. Of particular significance is the strong preference for rings over semi-solid systems [34,197] which should hopefully extend to vaginal microbicide products, since high levels of user acceptability/satisfaction generally correlate with user adherence.…”
Section: Acceptability and Adherencementioning
confidence: 99%
“…Numerous studies have reported high user acceptability of VRs for contraception and estrogen replacement therapy [29,30,[33][34][35]39,[197][198][199][200][201][202]. Of particular significance is the strong preference for rings over semi-solid systems [34,197] which should hopefully extend to vaginal microbicide products, since high levels of user acceptability/satisfaction generally correlate with user adherence.…”
Section: Acceptability and Adherencementioning
confidence: 99%
“…113 Compared with estradiol inserts (pessaries), the ring was equally efficacious in alleviating dysuria (76%), urge incontinence (58%), and stress incontinence (53%), but was much more acceptable (60% v 14%). 114 Patients preferred the vaginal ring to conjugated estrogen 115 or estriol cream 116 as well. Recurrent UTIs were less frequent in women using the ring compared with nonusers.…”
Section: Options For Low-dose Vaginal Therapymentioning
confidence: 99%
“…120 Felding et al 158 documented proliferative endometrial changes in two of 12 women using the 25-mg tablet for only 3 weeks. Ayton et al 115 reported that two of 194 women using the 8-mg estradiol ring for 12 weeks had bleeding and showed proliferative endometrium on biopsy. Five percent of the urogenital ring users had proliferation in the North American safety trial, with one hyperplasia detected in an endometrial polyp compared with 10% of conjugated equine estrogen cream users who showed proliferative changes but no hyperplasia at 12 weeks.…”
Section: Can Low Dose Estrogen Be Used Alone?mentioning
confidence: 99%
“…been shown to have a role in decreasing dryness, urinary urgency and dyspareunia [8,26]. Estrogen therapy has also been shown in a double blind randomised placebo controlled trial of bilaterally oophorectomised women to significantly improve women's sexual interest, arousal, and orgasm but did not change the frequency of sexual intercourse [34].…”
Section: Reviewmentioning
confidence: 99%